2017
DOI: 10.1093/annonc/mdx004
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of mutantKRAS in circulating exosome-derived DNA from early-stage pancreatic cancer patients

Abstract: Exosomes are a distinct source of tumor DNA that may be complementary to other liquid biopsy DNA sources. A higher percentage of patients with localized PDAC exhibited detectable KRAS mutations in exoDNA than previously reported for cfDNA. A substantial minority of healthy samples demonstrated mutant KRAS in circulation, dictating careful consideration and application of liquid biopsy findings, which may limit its utility as a broad cancer-screening method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
346
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(360 citation statements)
references
References 32 publications
11
346
2
1
Order By: Relevance
“…Most studies focus on the presence of ccfDNA mutations in one or two genes to compare their presence to clinical outcome [19, 20]. In our study, we sought to assess the mutation patterns in a broad set of genes to highlight tumor heterogeneity and demonstrate clonal evolution over the course of disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies focus on the presence of ccfDNA mutations in one or two genes to compare their presence to clinical outcome [19, 20]. In our study, we sought to assess the mutation patterns in a broad set of genes to highlight tumor heterogeneity and demonstrate clonal evolution over the course of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant KRAS ccfDNA was, however, found by others in 10 of 34 pancreatic patients (29%) [22] or in 136 of 188 (72.3%) of patients with metastatic PDAC [23]. Another study showed that mutant KRAS ccfDNA was detected in 14.8%, 45.5%, 30.8%, and 57.9% of age-matched controls, localized, locally advanced, and metastatic PDAC patients, respectively [20]. In circulating exosomal DNA the percentages of mutant KRAS in these groups were even higher, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Allenson and coworkers, who compared exosome-derived DNA to cfDNA in liquid biopsies of patients with pancreatic ductal adenocarcinoma, found higher percentage of detectable KRAS mutations in exosome DNA than previously reported for cfDNA. They isolated exosomes using serial ultracentrifugation and characterized them with electron microscopy, flow cytometry and particle analysis [141]. Concerns of contamination of protein/RNA/membrane aggregates arising from similarities in sedimentation properties during high-speed ultracentrifugation, have prompted some protocols to use sucrose density gradients or adjusting the centrifugation duration in a "swinging bucket" or "fixedangle" rotor for efficient separation of the exosomes from the protein-or lipid-aggregates [142,143].…”
Section: Methods To Isolate and Identify Exosomesmentioning
confidence: 99%
“…A well-established example is non-small-cell lung cancer where liquid biopsy can help in guiding the choice of suitable therapeutic regimens and are already included in the portfolio of routine clinical algorithms as of to date [90,91]. Apart from these applications, in pancreatic cancer, liquid biopsy techniques are thought to carry great potential for early detection and secondary prophylaxis [92,93,94]. …”
Section: Liquid Biopsymentioning
confidence: 99%